High-resolution ultrasound tendon-to-bone distances in partial and complete finger flexor A2 pulley ruptures simulated in human cadaver dissection: toward understanding imaging of partial pulley ruptures - Iruretagoiena, Xeber; Schöffl, Volker; Balius, Ramón; Blasi, Marc; Dávila, Fernando; Sala, Xavier; Sancho, Igor; De La Fuente, Javier (Frontiers in Bioengineering and Biotechnology, 2023)
The A2 pulley tear is the most common injury in rock climbing. Whereas complete A2 pulley ruptures have been extensively researched, studies focused on partial A2 pulley ruptures are lacking. A2 pulleys rupture distally to proximally. High-resolution ultrasound imaging is considered the gold-standard tool for diagnosis and the most relevant ultrasound measurement is the tendon-to-bone distance (TBD), which increases when the pulley ruptures. The purpose of this study was to establish TBD values for different sizes of partial A2 pulley ruptures and compare these values with those of complete ruptures. The sample consisted of 30 in vitro fingers randomly assigned to 5 groups: G1, no simulated tear (control); G2, simulated 5 mm tear (low-grade partial rupture); G3, simulated 10 mm tear (medium-grade partial rupture); G4, simulated 15 mm tear (high-grade partial rupture); and G5, simulated 20 mm or equivalent tear (complete rupture). A highly experienced sonographer blinded to the randomization process and dissections examined all fingers. The TBD measurements (medians and interquartile ranges) were as follows: G1, 0.95 mm (0.77-1.33); G2, 2.11mm (1.78-2.33); G3, 2.28 mm (1.95-2.42); G4, 3.06 mm (2.79-3.28); and G5, 3.66 mm (3.55-4.76). Significant differences were found between non torn pulleys and simulated partial and complete pulley ruptures. In contrast, and inconsistent with other findings, no significant differences were found among the different partial rupture groups. In conclusion, the longer the partial pulley rupture, the higher the TBD value. The literature is inconsistent regarding the TBD threshold to diagnose a partial A2 pulley rupture. The minimum TBD value for a partial rupture was 1.6 mm, and TBD values above 3mm suggest a high-grade partial pulley rupture (15mm incision) or a complete pulley rupture.